A Perception of z generation on halal brand personality in Indonesia - Kumala, Nafa Indah; Ali, Dini Salmiyah (Journal of Halal Product and Research (JHPR), 2023)
The growth of various halal industry sectors around the world is increasing year by year. However, halal fashion as the third rank still has a fairly slow growth compared to the Islamic finance sector and halal food as the first and second-ranked halal industry sectors. Indonesia, with the largest number of Muslims in the world, will certainly feel the impact and benefit from this growth. This research aims to the Z generation's perception of halal brand personality in Indonesia using the concept of halal brand personality from Ahmad (2015) which is adopted from Aaker's theory (1997) and contains 5 dimensions: purity, excitement, safety, sophistication, and righteousness. This research uses a descriptive qualitative method and the data collection using focused group discussions with 7 SOKA's Instagram followers and product users. The result showed that purity is perceived as pure and friendly, excitement as up-to-date, safety as feeling safe, sophistication as high-class, and righteousness as spiritual.